Microbiology : an introduction / Gerard J. Tortora, Berdell R. Funke, Christine L. Case - Tortora, Gerard J.
Previous edition: published as by Gerard J. Tortora, Berdell R. Funke, Christine L. Case. Boston: Pearson, 2016